Continuous synthesis of Zn2Al–CO3 layered double hydroxides: a comparison of bench, pilot and industrial scale syntheses. Issue 4 (8th March 2019) - Clark, I.; Gomes, R. L.; Crawshaw, C.; Neve, L.; Lodge, R.; Fay, M.; Winkler, C.; Hull, M.; Lester, E.
Abstract : Zn2 Al–CO3 was produced continuously at bench (g h −1 ), pilot (100s g h −1 ) and industrial scale (10s kg h −1 ). Abstract : Zn2 Al–CO3 was produced continuously at bench (g h −1 ), pilot (100s g h −1 ) and industrial scale (10s kg h −1 ). Crystal domain length and BET surface area were similar at all three scales although there was a small increase at pilot scale. Platelet size increased from 120 nm at bench to 177 nm and 165 nm at pilot scale and industrial scale, respectively. Overall this paper shows that the increase in scale by almost 2000× does not impact on the overall product quality which is an excellent indicator that continuous hydrothermal synthesis is a route for nanomaterials synthesis.